ANALISA KUALITAS UDARA DAN KELUHAN SALURAN PERNAPASAN SERTA KELUHAN IRITASI MATA PADA PEKERJA DI PETERNAKAN SAPI PT. PRIMA INDO MANDIRI SEJAHTERA BERASTAGI, SUMATERA UTARA TAHUN 2013 - rizki sarjani; surya dharma; indra chahaya (Lingkungan dan Kesehatan Kerja, 2014)
Dairy farm is one of the businesses that are still developing in Indonesia. The largest dairy farm in Northern Sumatra, is the dairy farms of PT Prima Indo Mandiri Sejahtera in Berastagi Karo Regency. Dairy farms can cause problems for the environment, one of which is the quality of the air. This research aims to know the air quality and complaint irritated eyes and respiratory tract complaints on the workers in the dairy farms of PT Prima Indo Mandiri Sejahtera, Berastagi, Indonesia by 2013. The type of research used is descriptive. Population in this research is 41 people workers that is used in total sampling. The results showed that the air quality of ammonia and hydrogen sulfide in dairy farms of PT Prima Indo Mandiri Sejahtera did not exceeded the level of the quality standard specified in KepMenLH No 50 in 1996. The highest point on range performed in a cage, they are 0,2002 for NH3 and H2S to 0,01289. Conclusion of this research is the quality of the air in the form of NH3 and H2S have not exceeded the quality standards. Based on the characteristics of workers are age, gender, work hours per day, working period, and smoking, there are 15 workers who have respiratory tract complaints and 12 people who have complaints of eye irritation. Therefore it's recommended to PT Prima Indo Mandiri Sejahtera to give self protective tools for workers at the nearby cow cages, improving the cleanliness of the cages and conduct air monitoring on an ongoing basis.